Mga monumento ni Eman Eman's monuments - Evasco, Eugene Y.; Ranola, Jonathan G.; Bravo, Becky (Quezon City Lampara Publishing House, Inc., 2014)
"Eman is a child who lives in a place where there is a monument. One time he asks his mother why there are monuments. Why is there a need to erect monuments? His mother gladly explains to him. An so Eman and his playmates also erect their own monuments. Find out in this story what monuments really mean and why things should be cared for for the kids of generations to come."
Stories with moral values.
Donated by Eugene Y. Evasco.
Text in Filipino and English.
Keywords: Monuments